2004
DOI: 10.1007/s00380-004-0776-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum interleukin-6 and high-sensitivity C-reactive protein levels in patients with acute coronary syndrome and their responses to simvastatin

Abstract: The role of inflammation in acute coronary syndrome (ACS) and the mechanism by which statin treats ACS is explored. Serum high-sensitivity C-reactive protein (hs-CRP) and interleukin-6 (IL-6) levels were measured in 50 patients with ACS [including 30 cases with unstable angina (UA) and 20 patients with acute myocardial infarction (AMI)], 34 patients with stable angina (SA), and 30 controls. Patients in the ACS group were randomly assigned to a simvastatin group (including a simvastatin AMI subgroup, n = 11 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 8 publications
1
10
0
1
Order By: Relevance
“…These findings are echoed in earlier studies. 39,41,[49][50][51][52][53] Mizia-Stec et al 39 found that there was an increase in TNF-α levels in patients with AMI. Luo et al 50 reported elevated levels of serum IL-6 in patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are echoed in earlier studies. 39,41,[49][50][51][52][53] Mizia-Stec et al 39 found that there was an increase in TNF-α levels in patients with AMI. Luo et al 50 reported elevated levels of serum IL-6 in patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that the development of atherosclerotic plaque is associated with inflammation and that the measurement of this inflammation has predictive value in determining risk for future thrombotic events (Ross, 1993;Tracy, 1997;Tracy et al, 1997;Luo et al, 2004). Markers of low-grade inflammation associated with heart disease include CRP, TNF-a and IL-6 (Luo et al, 2004;Chirinos et al, 2005).…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…Markers of low-grade inflammation associated with heart disease include CRP, TNF-a and IL-6 (Luo et al, 2004;Chirinos et al, 2005). Individuals with low risk of heart disease have low levels of these markers of inflammation, whereas those with high risk have high levels of these markers.…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…Also ACS and AMI are accompanied by an acute inflammatory response and increased levels of CRP, acute phase proteins [1], and IL-6 [10]. In a study comparing stable angina pectoris (SAP) and unstable AP (UAP), the IL-18 concentrations tended to be higher in the UAP group; conversely, IL-10 concentrations were significantly lower [11].…”
Section: Discussionmentioning
confidence: 99%